Gempa bumi padang panjang tahun 1926 dan dampaknya terhadap gerakan komunis di Sumatra Barat - Etmi Hardi; Fikrul Hanif Sufyan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study aims to analyze the impact of the 1926 Padang Panjang earthquake on the dynamics of the communist movement in West Sumatra, particularly the development of the Kuminih ideology and the revolutionary movement leading to the Silungkang uprising of 1927. This research employed the historical method through four stages: heuristics, source criticism, interpretation, and historiography. Primary sources were obtained from colonial newspapers, archival documents, and records from the Minangkabau Cultural Information and Documentation Center, while secondary data were collected from books and scholarly studies relevant to the topic. The findings reveal that the 1926 earthquake not only caused extensive physical destruction and casualties in Padang Panjang and surrounding regions but also temporarily reduced ideological tensions between Islamic modernist groups and communist movements. However, during the colonial government’s post-earthquake recovery efforts, communist networks reorganized and continued preparing revolutionary actions in strategic areas such as Silungkang and Sawahlunto. This study demonstrates that natural disasters significantly influenced political consolidation, social conflict, and revolutionary movements in colonial West Sumatra.